The STORY Model for Parent–Madrasah Collaboration in Character Education - Wahyuni Wahyuni; Toto Suharto; Fauzi Muharom (ARZUSIN, 2026)
Although parent–madrasah collaboration plays a critical role in strengthening character education within Islamic educational contexts, research specifically addressing its managerial model remains limited. This study aims to formulate the STORY Model as a conceptual framework for managing parent–madrasah collaboration in character education. Employing a conceptual literature review design, this study examined purposively selected scholarly works on family–school partnerships, parental involvement, character education, Islamic educational management, and madrasah governance. Data were collected through document-based literature review and analyzed using thematic synthesis. The findings reveal three major patterns of collaboration: educational communication, family participation in madrasah programs, and value reinforcement at home. The analysis also identifies several managerial weaknesses, including administratively oriented communication, reactive parental involvement, unstructured participation, limited reflective monitoring, and unclear character indicators. The study concludes that the STORY Model offers a systematic, participatory, and character-oriented framework for transforming parent–madrasah collaboration into a pedagogical partnership. The contribution of this study lies in advancing conceptual discourse on Islamic educational management and providing a foundation for future empirical validation across diverse madrasah contexts.